Biological response to 5 years of operations of cascade rubber dams in a plateau urban river, China. (30th June 2020) - Mao, Xufeng; Wei, Xiaoyan; Engel, Bernard; Wang, Wenying; Jin, Xin; Jin, Yanxiang
Abstract: Aquatic ecosystem response to dam construction and operation is an important concern, but systematic assessment of impacts induced by cascade small rubber dams are seriously lacking. In this study, the Huangshui River in Qinghai Province was selected to investigate biological response to small cascade rubber dams. Two years of monitoring data in 2018 and 2019 were utilized to quantify the variation of five kinds of aquatic organisms. Results indicate continuous rubber dams produced significant changes to hydrological regimes of rivers, especially for high flow seasons, and further affect aquatic biological populations and structures of the river. (a) The biodiversity and biomass of plankton increased by 8.0 times and 1.8 times, respectively; the biomass of fish and benthic animals were enhanced by 3.2 and 2.1 times, respectively, but the species richness decreased by 30% on average. Native fish are completely replaced by exotic fish, and benthic animals are changing towards singularity; (b) The surface and bottom food chains of the river gradually become dominant, and the disappearance of native fish in the middle layer caused the exchange flow in the middle layer to decrease rapidly, which leads to a dumbbell‐shaped distribution structure of biomass; (c) The regulation services of rivers have also undergone huge changes. N2 O and CH4 emissions from dammed areas have increased by 10.1 times, and the water purification function varied in different dammed areas.